New Editors; TelSoc’s first year; and Australia’s hunger for networked data - Gerrand, Peter (Journal of Telecommunications and the Digital Economy, 2014)
A welcome to this Journal’s two new editors; congratulations to the Journal’s publisher, TelSoc, on its first year of operation; and observations on the continuing hunger in Australia for networked data, of which Big Data (our major theme for this issue) will be an important future component.